Una aplicación de la teoría del comportamiento planificado al segmento masculino latinoamericano de productos de cuidado personal - Regalado Pezúa, Otto (2017)
This research study identifies those factors which influence the consumption of care products in the Latinamerican male segment. That's why, an instrument based on the behavorial theory was applied to 600 men living in two countries of this región and having different levels of development regarding the above mentioned category, Mexico -highly developed- and Peru -moderately developed-. The data obtained were analyzed using a model of structural equations. The results show that a subjective norm will stop men's consumption of these kinds of products. Similarly, the impact of this subjective norm will be lower in young men, allowing them to have a great aperture in the consumption of these care products.